Dissociative experiences in individuals with subclinical psychosis and a history of developmental trauma: a qualitative study - Eirini Aikaterini Melegkovits; Ava Mason; Jordan Reid; Hind Akooly; Paul Jung; Michael Bloomfield (European Journal of Psychotraumatology)
Background: Among individuals with psychotic experiences, those with a history of developmental trauma face greater symptom severity and worse clinical outcomes compared to those without. Dissociation constitutes a prominent, characteristic of this group’s clinical presentation, whose nuances and associated characteristics remain however understudied in psychosis research. We aimed to address this gap by conducting a qualitative study to investigate the phenomenology, context, and impact of dissociative experiences in individuals with subclinical psychosis and a history of developmental trauma.Methods: 25 UK-based participants with a history of developmental trauma and meeting criteria for subclinical psychosis, based on the CAPE-15, were recruited via social media. Participants attended semi-structured interviews online, which were transcribed verbatim and analysed with thematic analysis by two researchers.Results: Thematic analysis yielded the following themes: (1) Phenomenology of Dissociation; (2) Context of Dissociation; (3) Impact of Dissociation; (4) Dissociation and Psychotic-like Phenomena. Participants described experiences of detachment and compartmentalisation, which when experienced were confusing and often distressing. Dissociation was linked to affective experiences, their history of developmental trauma and psychotic-like experiences.Conclusion: This study elucidates the complex and varied nature of dissociative experiences in individuals with subclinical psychosis with a history of developmental trauma. These findings highlight the need for further research to understand the manifestation of dissociation in this population and the links with distress and other aspects of psychopathology. Importantly, it is essential to use this understanding to inform the development of interventions and improve clinical recognition and management.